A Theory of Policy Reversal - Robert A.J. Dur; Otto H. Swank (Tinbergen Institute, 1997)
After decades of government growth, Western countries have witnessed major policy reversals. Prominent examples include the far-reaching policy reversals implemented by Thatcher, Reagan, and Douglas. This paper offers an explanation for these policy reversals. Our key argument rests on the assumptions that public decisions are made by majority rule and that voters have incomplete information about the aggregate consequences of all possible bundles of public projects making up the government. Unlike existing explanations, our theoryis consistent with the observations that policy reversals are often undertaken simultaneously and that separate parts of the package of policy reversals are not welcomed enthusiastically by voters.
Keywords: D78; H50; 330; Policy reversal; Majority voting; Size of the government; Deregulierung; Haushaltskonsolidierung; Staatsquote; Abstimmungsregel; Neue politische Ökonomie; Unvollkommene Information; Theorie